JUSTICE AND LEGAL CERTAINTY AS A MANIFESTATION IN THE CONTEXT OF CONSTITUTIONAL LAW - Pakpahan, Zainal Abidin (Universitas Labuhanbatu, 2025)
This journal aims to explore and analyze the relationship between justice and legal certainty in the context of Indonesian constitutional law. Using normative juridical methods, this study identifies the challenges faced in realizing both concepts amidst complex social and political dynamics. The formulation of the problem that arises in this study is about how the relationship between justice and legal certainty in the constitutional law system and what are the challenges faced in realizing justice and legal certainty in Indonesia. The results of the study indicate that community involvement in the legal process and institutional strengthening are key factors in achieving equitable justice. In addition, this study emphasizes the need for more effective legal aid programs and active citizen participation in legal decision-making. These findings are expected to provide valuable insights for the development of more inclusive and equitable legal policies in Indonesia, as well as encouraging the creation of a more democratic society. Keywords: Justice, Certainty, Law, Order, State